Online consumers' satisfaction in self-collection: value co-creation from the service fairness perspective - Wang, Xeuqin (2022)
E-commerce logistics services are increasingly offering innovative solutions that invite consumers’ co-creation. Although value co-creation empowers consumers, it also connotes a sense of exploitation. This study explores the fairness perspective of co-creating satisfactory logistics services, using self-collection service as an example. A theoretical model based on synthesized insights of Fairness Heuristics and Selective Information Processing was conceptualized and validated. Survey data were collected from 680 actual self-collection users. The findings show a three-pronged service evaluation process with consumers’ fairness perception as a central anchorage. Furthermore, the satisfaction formation process is moderated by consumers’ pre-formed beliefs leading to biased evaluations of co-creation experiences. This study contributes to literature with a contingent framework of consumers’ participation in logistics services, suggesting a heuristic-based process of value co-creation among the consumers. We also create practical insights on consumers’ preformed beliefs toward the logistics services and service providers that lead to a biased satisfaction formation process.